Monte-Carlo simulation of response of semiconductor detectors for radionuclide identification devices - Skrypnyk, A.I.; Khazhmuradov, M.A. (Вопросы атомной науки и техники, 2015)
Wide band-gap semiconductor detectors have good application prospects in the compact systems intended for detecting low-level radiation and identifying radionuclides. In the present work, the algorithm of identification of radionuclides and determination of their quantitative characteristics was researched. The responses of CdZnTe- and TlBr-detectors to radiation from ¹³⁷Cs, ⁹⁰Sr, ⁴⁰K, ¹³¹I and ⁶⁰Co were simulated by Monte-Carlo method via GEANT4 v. 4.9.6 package for realization of this algorithm. It allowed us to create a databases of spectral signatures for the investigated detectors and to use them as input data for the regression model.